Two Saccharomyces cerevisiae genes which control sensitivity to G1 arrest induced by Kluyveromyces lactis toxin. - Butler, A R (1994)
The Kluyveromyces lactis toxin causes an arrest of sensitive yeast cells in the G1 phase of the cell division cycle. Two complementary genetic approaches have been undertaken in the yeast Saccharomyces cerevisiae to understand the mode of action of this toxin. First, two sequences conferring toxin resistance specifically in high copy number have been isolated and shown to encode a tRNA(Glu3) and a novel polypeptide. Disruption of the latter sequence in the yeast genome conferred toxin resistance and revealed that it was nonessential, while the effect of the tRNA(Glu)3 was highly specific and mediated resistance by affecting the toxin's target. An alpha-specific, copy number-independent suppressor of toxin sensitivity was also isolated and identified as MATa, consistent with the observation that diploid cells are partially resistant to the toxin. Second, in a comprehensive screen for toxin-resistant mutants, representatives of 13 complementation groups have been obtained and characterized to determine whether they are altered in the toxin's intracellular target. Of 10 genes found to affect the target process, one (KTI12) was found to encode the novel polypeptide previously identified as a multicopy resistance determinant. Thus, both loss of KTI12 function and elevated KTI12 copy number can cause resistance to the K. lactis toxin.